Katsaus yhteiskunnalliseen yrittäjyyteen matkailussa: osallisuuden mahdollisuudet pohjoisen urbaaneissa paikallisyhteisöissä - Minni Haanpää; Maria Hakkarainen; Anu Harju-Myllyaho (Matkailututkimus, 2018)
The purpose of this literature review is to explore how social entrepreneurship research is conducted in the field of tourism and to consider the possibilities, limitations and challenges, which are included in it in urban, northern environment. Social entrepreneurship in tourism can be attached to a larger context of the inclusion and possibilities of inclusion, which are in tourism research discussed in terms of social and inclusive tourism. The impact of social entrepreneurship is namely on the social: communities and societies. It aims in producing meaningful influence besides economic benefit to the society. In this review, we first explore how social entrepreneurship is discussed in the field of tourism research. We also reflect what kind of viewpoints the discussions offer to social entrepreneurship in tourism in the northern, urban context. Based on the review, the central terms of social entrepreneurship in tourism are value creation, social innovations and sustainability. The aim of the social enterprises in tourism is especially to develop the living conditions of the community through, for instance, creating jobs, increasing the employability of those at risk of exclusion and supporting communities in the periphery. The social enterprises are studied very little in the context of urban north since the studies focus on rural destinations.